Concise enantioselective synthesis of (R)-selegiline, (S)-benzphetamine and formal synthesis of (R)-sitagliptin via electrophilic azidation of chiral imide enolates - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise and high yielding enantioselective synthesis of (R)-selegiline, an anti-Parkinson's drug, (S)-benzphetamine, an anti-obesity agent, and (S)-sitagliptin, an anti-diabetic drug has been described starting from commercially available starting materials employing Evans' electrophilic azidation of chiral imide enolates as a key chiral inducing step, which proceeds in a highly diastereoselective manner (>99%). (C) 2014 Elsevier Ltd. All rights reserved.